2021
DOI: 10.5194/acp-2021-703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The nitrate radical (NO<sub>3</sub>) oxidation of alpha-pinene is a significant source of secondary organic aerosol and organic nitrogen under simulated ambient nighttime conditions

Abstract: Abstract. The reaction of α-pinene with NO3 is an important sink of both α-pinene and NO3 at night in regions with mixed biogenic and anthropogenic emissions; however, there is debate on its importance for secondary organic aerosol (SOA) and reactive nitrogen budgets in the atmosphere. Previous experimental studies have generally observed low or zero SOA formation, often due to excessive [NO3] conditions. Here, we characterize the SOA and organic nitrogen formation from α-pinene + NO3 as a function of nitrooxy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…α-Pinene is the most abundant biogenic monoterpene globally, but previously measured SOA mass yields from its NO 3 oxidation are inconsistent, ranging from 0 to 25%. This latter and highest yield was found at low temperature, 5 °C, and >100 μg m –3 background OA. The generally lower SOA mass yields from α-pinene + NO 3 are in stark contrast with the higher values from reaction of NO 3 with other monoterpenes …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…α-Pinene is the most abundant biogenic monoterpene globally, but previously measured SOA mass yields from its NO 3 oxidation are inconsistent, ranging from 0 to 25%. This latter and highest yield was found at low temperature, 5 °C, and >100 μg m –3 background OA. The generally lower SOA mass yields from α-pinene + NO 3 are in stark contrast with the higher values from reaction of NO 3 with other monoterpenes …”
Section: Introductionmentioning
confidence: 99%
“…43−45 Recent work on the NO 3 + α-pinene system probing RO 2 fate dependence showed large yields under certain conditions, which they attributed to dominance of RO 2 + RO 2 reactions, with an estimated SOA mass yield of ∼65% for that pathway and negligible SOA for other RO 2 fates. 31 Given the uncertainties in atmospheric RO 2 fate, we examine how these different fates affect SOA formation from NO 3 oxidation of terpenes. Specifically, we sought to determine if the observed anomalously low α-pinene SOA yield was unique to particular RO 2 fates or chamber artifacts, by performing experiments across three different putative RO 2 fates, RO 2 + NO 3 , RO 2 + RO 2 , and RO 2 + HO 2 , and using a range of inorganic and organic seed aerosol concentrations (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although in a low NO x atmosphere these RO 2 • radicals could also react with HO 2 or NO 3 radicals or isomerize (reaction with NO is unlikely since NO rapidly titrates NO 3 radicals), all the bimolecular reactions can lead to many of the same products, 21 and the formation of low-volatility ROOR dimers through RO 2 • + RO 2 • reactions is currently a topic of much interest. 22 For example, photochemical modeling by Bates et al 23 designed to mimic nighttime chemistry during the 2013 SOAS campaign indicated that ∼20% of RO 2 • radical reactions occurred with other RO 2 • radicals and that ROOR products were formed with a branching ratio of ∼18%. Conducting experiments in this regime also greatly simplifies the development of reaction mechanisms and can provide a useful point from which to perturb the chemistry into other, less well understood regimes, under controlled conditions.…”
Section: ■ Introductionmentioning
confidence: 99%